The Three Hundred Project: The evolution of galaxy cluster density profiles. Issue 3 (6th December 2018) - Mostoghiu, Robert; Knebe, Alexander; Cui, Weiguang; Pearce, Frazer R; Yepes, Gustavo; Power, Chris; Dave, Romeel; Arth, Alexander
Abstract: Recent numerical studies of the dark matter density profiles of massive galaxy clusters ( M halo > 10 15 M⊙ ) show that their median radial mass density profile remains unchanged up toz > 1, displaying a highly self-similar evolution. We verify this by using the data set of theThe Three Hundred project, i.e. 324 cluster-sized haloes as found in full physics hydrodynamical simulations. We track the progenitors of the mass-complete sample of clusters atz = 0, and find that their median shape is already in place byz = 2.5. However, selecting a dynamically relaxed subsample (∼16 per cent of the clusters), we observe a shift of the scale radius rs towards larger values at earlier times. Classifying the whole sample by formation time, this evolution is understood as a result of a two-phase halo mass accretion process. Early-forming clusters – identified as relaxed today – have already entered their slow accretion phase, hence their mass growth occurs mostly at the outskirts. Late-forming clusters – which are still unrelaxed today – are in their fast accretion phase, thus the central region of the clusters is still growing. We conclude that the density profile of galaxy clusters shows a profound self-similarity out to redshiftsz ∼ 2.5. This result holds for both gas and total density profiles when including baryonic physics, as reported here for two rather distinct sub-grid models.